Speaking Materials' Eligibility Standard in "Bahasa Inggris Kelas XI SMK" Textbook - Hasibuan, Filza Irawan (TRANSFORM: Journal of English Language Teaching and Learning, 2025)
This study evaluates the speaking materials within the “Bahasa Inggris Kelas XI SMK” textbook, acknowledging its critical role in fostering practical communication skills for the workforce as mandated by the Indonesian national curriculum. The primary aim is to assess the eligibility of these materials against five key criteria proposed by Tomlinson (2011): authenticity, relevance, engagement, support, and variety. Employing a descriptive qualitative methodology with a document analysis approach, the research systematically examines the textbook’s content using a checklist-based assessment. The findings reveal that the textbook substantially fulfills these eligibility standards. It demonstrates strong authenticity through dialogues and tasks that mirror real-world communication, high relevance by providing activities with clear communicative goals, and effective engagement and support via structured, interactive excercises that build learner confidence. However, a significant limitation was identified in the criterion of variety. The analysis indicates a notable scarcity of activities explicitly designed for auditory and kinesthetic learning styles, with materials predominantly catering to visual learners. This study concludes that while the textbook serves as a valuable resource, its future iterations would benefit significantly from the integration of more diverse activities to ensure greater inclusivity and effectiveness for all learning preferences.